STUDI EKSPERIMENTAL KOMPOR PORTABEL BERBAHAN BAKAR OLI BEKAS DENGAN VARIASI JUMLAH LUBANG NOZZLE DAN DEBIT UDARA TERHADAP DISTRIBUSI TEMPERATUR: EXPERIMENTAL STUDY OF THE INFLUENCE OF THE NUMBER OF NOZZLE HOLES AND AIR DISCHARGE ON TEMPERATURE DISTRIBUTION IN USED OIL-FUEL PORTABLE STOVES - Mochammad Farhan Aprilianto; Satworo Adiwidodo (Jurnal Teknik Mesin, 2025)
The use of motorized vehicles increases the amount of used oil produced. This study aimed to determine the effect of variations in the number of nozzle holes and air discharge on temperature distribution. Research using experimental methods to determine the effect of the number of nozzle holes and air volumetric flow rate on temperature distribution on portable stoves. Data from flame temperature measurements using thermocouple and thermogun tools, with repetition 3 times. Data analysis used factorial ANOVA to see the interaction between the independent variables on the dependent variable. The results show the lowest point of the flame at the number of holes 25 with a temperature of 544 ˚C and the highest point at the number of holes 20 with a temperature of 792 ˚C. In the air discharge variation, the lowest point of flame is at 0.002 mᶟ/s air discharge with a temperature of 463 ˚C and the highest point is at 0.006 mᶟ/s air discharge with a temperature of 793 ˚C.